DETERMINING PURCHASE INTENTION IN HALAL PERSONAL CARE PRODUCT: STUDY ON MUSLIMAH MILLENNIAL GENERATION - Mahliza, Febrina; Prasetya, Prita (Universitas Brawijaya, Indonesia, 2021)
Currently, Indonesian citizens were mostly dominated by the millennial generation. The domination of this generation became a potential market for a halal product. However, millennials considered having less interest to dig more information about the